Modelling structural deformations in a roasting coffee bean. (April 2019) - Fadai, Nabil T.; Please, Colin P.; Van Gorder, Robert A.
Abstract: Macroscale deformations in a roasting coffee bean are important mechanisms in determining flavour development, moisture loss, and consistency of the bean. In this paper, we model the stresses and strains in the cellulose structure of a roasting coffee bean via temperature-dependent poroviscoelastic constitutive equations. This model accounts for the deformations that are created and controlled by the moisture content, temperature, and gas pressure inside of the roasting coffee bean. The model combines previously derived multiphase heat and mass transfer models for roasting coffee beans with these poroviscoelastic equations, to determine when and where macroscale deformations of the cellular matrix are likely to occur. By exploiting reasonable asymptotic reductions of the poroviscoelastic equations, we find that a large surge of stress is produced in the interior of a coffee bean. We determine that this build-up of stress is due to the viscoelastic interior of the bean being contained by a rigid elastic exterior and unable to expand. Our theoretical results suggest directions for possible improvement in standard industrial coffee roasting techniques, which may allow the macroscale deformations of the cellular matrix to be controlled and thereby improve properties such as flavour, moisture loss, and consistency of the final product. Highlights: The cellulose structure in a roasting coffee bean is modelled. The governing equations describing the cellulose structure are coupled to existing multiphase models. Analysis of the aforementioned equations reveals a surge of internal stresses.